2019
DOI: 10.1016/j.jmbbm.2018.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Crack initiation from a clinically relevant notch in a highly-crosslinked UHMWPE subjected to static and cyclic loading

Abstract: Crosslinked Ultra High Molecular Weight Polyethylene (UHMWPE), which is used as a bearing material in total joint replacement components, is subjected to static and cyclic loads in vivo.Resistance to crack initiation from a notch as a function of static and cyclic loads is not well understood for crosslinked UHMWPE. This study estimated the resistance of crosslinked UHMWPE (crosslinked with 100 kGy gamma radiation and remelted to extinguish free radicals) to crack initiation for a clinically relevant notch und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…There remain some potential obstacles to the application of the approach, such as difficulty in obtaining unique values of the material parameters in the constitutive model. In addition, the findings in a previous study by the authors [12] of distributed multi-layer crack initiation over the notch root surface [10, 12] presents a situation that potentially violates the assumption of J-integral as the only driving force of crack phenomena in UHMWPE.…”
Section: 5: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remain some potential obstacles to the application of the approach, such as difficulty in obtaining unique values of the material parameters in the constitutive model. In addition, the findings in a previous study by the authors [12] of distributed multi-layer crack initiation over the notch root surface [10, 12] presents a situation that potentially violates the assumption of J-integral as the only driving force of crack phenomena in UHMWPE.…”
Section: 5: Discussionmentioning
confidence: 99%
“…From a design standpoint, crack initiation from a clinically relevant notch condition is of more interest than crack initiation from a razor sharp condition which has been previously studied [9]. In a previous study by the authors [10], crack initiation from a notch with a radius of 0.25 mm was studied with consideration of the Williams’ viscous fracture model [11]. Further, we have noted that a time dependent power law, the Williams model (equations 1 and 2) appears to govern crack initiation and propagation in this material [12].…”
Section: 2: Introductionmentioning
confidence: 99%
“…In orthopaedic applications, the most critical form of damage in UHMWPE is not fatigue crack growth, but wear. The problem is most acute in knee joint replacements, which not only suffer losses of material from heavily loaded bearing surfaces, but also generate wear debris particles, which have diameters mainly in the range 0.1 to 10 μmsee Part 3 in this series [10][11][12][13]. The body's immunological response to these particles is complex; it includes both inflammation and bone loss (osteolysis), which in the most severe cases leads to loosening of the implant and the need for replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, great effort has been put on the research of FCG of UHMWPE and its modified materials. Sirimamilla and Rimnac () investigated the effects of loading conditions (static and cyclic loading) on crack initiation and propagation behavior of cross‐linked UHMWPE considering different loading frequencies and waveforms. The results suggested that crosslinked UHMWPE was more resistant to crack initiation from a notch under static loading conditions compared with fatigue loading conditions.…”
Section: Introductionmentioning
confidence: 99%